ANALYZING EFL CLASSROOM INTERACTION IN CONTEXTUAL TEACHING AND LEARNING AMONG CLASS MEMBERS - Ratnawati Ratnawati; Romdah Romansyah (University of Muhammadiyah Malang, 2022)
Face-to-face class interaction is extraordinary matter dealing with the new normal of the COVID-19 pandemic. However, there has not been various preliminary research and works of literature related to face-to-face interactions in English language learning after the COVID-19 break, especially with contextual teaching and learning approach. Thus, the present study aims at exploring the interaction process among teachers and students in the learning process in an academic atmosphere and classify the types of classroom interactions implemented during the meetings. The method of current research was a case study and used instrument of video recording from participant observation conducted in classroom activities. The research data showed that the interaction process among teachers-students, and students-students ran well throughout the REACT (reflecting-engaging-activating-cooperating-transferring) instructional stages of contextual teaching and learning eventhough some students experienced that learning English was their first experiences in the new normal of the face-to-face meeting. Some pattern interactions were also clearly described and discussed regarding the type of classroom interaction. From the results that have beenelaborated, other researchers are also recommended to apply the sameinteraction pattern in any educational levels. Research limitations andimplications are also discussed as well in the session.